A novel combination of the 'adaptive research' methodology with the Learning Alliance approach - CGIAR Research Program on Rice (2018)
Completed a comparative analysis of the learning process induced by adaptive research (AR) in one case and a combined AR with Learning Alliance (LA) approach in another.